Der gesellschaftliche Umgang mit zunehmender Verwundbarkeit: eine Analyse der sozialen Bedingungen für vulnerabilitätsorientierte räumliche Planung in den Küstenzonen von Bangladesch - Mallick, Bishawjit (Regionalwissenschaftliche Forschungen = Regional Science Research, 2013)
How respond the societies in developing countries to natural hazards, particularly in the areas of prevention and management? Which of the identified adaptation measures are socially acceptable and which are critical weaknesses of the existing spatial planning processes? How can this be solved? With the help of an empirical survey in the southwestern coastal area the present study aimed at to answer these questions.